Evaluation of the Impact of the Program Keluarga Harapan Through Pertemuan Peningkatan Kemampuan Keluargas - Winarno, Bambang Suko; Mardhalena, Azrita; Nugrahaningsih, Nurfitri (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2025)
The study aims to evaluate the impact of the Program Keluarga Harapan (PKH) through Family Development Session (FDS/P2K2) in Kubu Raya Regency, present a relevant and significant area of research. This poverty alleviation initiative is expected to contribute to efforts in reducing poverty rates and improving the capabilities of low income families. The initial problems identified include changes in the mindset and behavior of beneficiaries in accessing health and education services before and after participacing the PKH program, limited participation of beneficiaries in fulfilling their obligations to attend Family Development Session (FDS/P2K2), the tendency of beneficiaries to use PKH assistance primarily for consumptive needs and to remain dependent on the assistance, also the emerging impacts of P2K2 implementation in Kubu Raya Regency. The writing of this thesis aims to determine the impact of P2K2 on changes the mindset and behavior of beneficiaries through P2K2 in Kubu Raya Regency. Data were obtained through interviews conducted with various predetermined subjects, namely PKH beneficiaries, PKH social assistants, social assistance coordinators, and the head of the Social Service Office of Kubu Raya Regency. The results of this study indicate that the impact of P2K2 requires further optimization to ensure that beneficiaries can consistently access health and education services. Beneficiaries attendance in P2K2 activites is generally satisfactory; however, participation of elderly beneficiaries remains low and requires improvement. Beneficiaries remain dependent on PKH assistance; therefore, training and empowerment programs are necessary to promote self reliance. In the short term, the impact of PKH is primarily limited to fulfilling consumptive needs, whereas medium and long-term impacts require sustained efforts through the collaboration of all PKH implementing stakeholders in Kubu Raya Regency.